2012
DOI: 10.5194/hess-16-201-2012
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of soil moisture and river flows over France for the spring season

Abstract: Abstract. Sources of spring predictability of the hydrological system over France were studied on a seasonal time scale over the 1960-2005 period. Two random sampling experiments were set up in order to test the relative importance of the land surface initial state and the atmospheric forcing. The experiments were based on the SAFRAN-ISBA-MODCOU hydrometeorological suite which computed soil moisture and river flow forecasts over a 8-km grid and more than 880 rivergauging stations. Results showed that the predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 46 publications
5
51
1
1
Order By: Relevance
“…The combination of ESP and Rev-ESP includes the two end points of no FS and perfect FS. Variations of the ESP/Rev-ESP approach have since been used in recent studies such as Li et al (2009), Shukla and Lettenmaier (2011), Paiva et al (2012 and Singla et al (2012) …”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…The combination of ESP and Rev-ESP includes the two end points of no FS and perfect FS. Variations of the ESP/Rev-ESP approach have since been used in recent studies such as Li et al (2009), Shukla and Lettenmaier (2011), Paiva et al (2012 and Singla et al (2012) …”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Hydrologic predictability at seasonal lead times (1 to 6 months) is derived from knowledge of initial hydrologic conditions (IHCs), which includes soil moisture (SM), snow water content (SWE), ground water and surface water (Paiva et al, 2012;Singla et al, 2012;Rosenberg et al, 2013) and seasonal climate forecast skill (FS) of meteorological variables like temperature, precipitation. In the past, numerous studies have investigated the contributions of the IHCs and/or FS in seasonal hydrologic predictability over different regions of the globe.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Wood and Lettenmaier (2008) applied the assessment framework over two river basins in the western USA and found that ICs yield streamflow forecasting skill for up to 5 months over northern California during the transition period between the wet and dry seasons but have less impact over southern Colorado basin due to a weaker annual cycle of precipitation. Since then, the revESP framework has been widely used to assess the role of ICs at regional to global scales (Li et al, 2009;Koster et al, 2010;Shukla and Lettenmaier, 2011;Paiva et al, 2012;Singla et al, 2012;Shukla et al, 2013;Yossef et al, 2013;Staudinger and Seibert, 2014;Yang et al, 2014). However, most assessments did not explicitly investigate the role of the IC of the surface water state variables in the streamflow forecasting, where it could be a major source of hydrological forecast uncertainty over rivers with low slope and large floodplains (Paiva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods were also used in conjunction with the multimodel ensemble forecasting framework that helps in determining the probability of exceedances of various thresholds useful for the water resource management (Regonda et al, 2006;Bracken et al, 2010). Existing studies also show that multimodel ensemble forecasts tend to perform much better than a singlemodel forecast, particularly in short-term and seasonal climate forecast (Krishnamurti et al, 1999(Krishnamurti et al, , 2000Rajagopalan et al, 2002;Hagedorn et al, 2005;Wood and Lettenmaier, 2006;Singla et al, 2012). Other alternative statistical techniques to multiple-regression models have also gained wider acceptance in many hydrologic applications, including artificial neural networks (ANN), genetic algorithms, multivariate adaptive regression splines, and partial least squares (Risley et al, 2001).…”
Section: Pal Et Al: Predictability Of Western Himalayan River Flowmentioning
confidence: 99%